Unilateral electronegative ERG of non-vascular aetiology. Issue 12 (18th November 2005) - Robson, A G; Richardson, E C; Koh, A H C; Pavesio, C E; Hykin, P G; Calcagni, A; Graham, E M; Holder, G E
Abstract : Background: Full field and pattern electroretinograms (ERG, PERG) are performed to assess generalised retinal function and macular function, respectively. An (electro) negative full field ERG usually describes an ISCEV standard maximal response in which the b-wave is smaller than a normal or minimally reduced a-wave and indicates dysfunction that is post-phototransduction. The most common cause of a unilateral negative ERG is central retinal artery occlusion (CRAO) or birdshot chorioretinopathy (BCR). This study examines the clinical and electrophysiological features of patients with unilateral negative ERG who do not have CRAO or BCR. Methods: 12 patients were ascertained with a unilateral negative ERG in whom a vascular aetiology and BCR were excluded. Most presented with symptoms of central retinal dysfunction. In 11 of the 12 patients additional long duration photopic stimuli were used to test cone system ON and OFF responses. Results: All 12 patients had unilateral electronegative bright flash full field ERGs indicating total or relative preservation of rod photoreceptor function, but dysfunction post-phototransduction. Seven of these patients had non-specific inflammatory changes in the eye with the negative ERG. Six patients, including five with inflammatory signs, had involvement of the cone ON response with complete preservation of cone OFF responses. A further three patients showed evidence of cone ON response abnormality with less severe OFF response involvement. Conclusion: The ERGs in this heterogeneous group of patients predominantly showed post-phototransduction involvement of the ON pathways. Sparing of the cone OFF response was often observed. The majority of patients had signs of previous inflammation and it is speculated that these highly unusual unilateral changes may be mediated via an autoimmune mechanism.